2016
DOI: 10.1111/trf.13716
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of syncopal‐type reactions after whole blood donation: a cluster‐randomized trial assessing hydration and muscle tension exercise

Abstract: Drinking 500mL of water or isotonic drink close to phlebotomy is useful in preventing presyncopal or syncopal reactions in blood donors. Isotonic drinks have the advantage of preventing delayed reactions and tiredness after whole blood donation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 38 publications
4
46
0
2
Order By: Relevance
“…In this issue of TRANSFUSION , Morand et al report a large, randomized controlled trial of two different mechanisms to prevent syncope during and after whole blood donation. The authors found that drinking 500 mL of water or isotonic drink before the donation was useful in preventing (pre)syncopal reactions in donors, whereas isotonic drinks had the advantage of preventing delayed reactions and fatigue after the donation.…”
mentioning
confidence: 99%
“…In this issue of TRANSFUSION , Morand et al report a large, randomized controlled trial of two different mechanisms to prevent syncope during and after whole blood donation. The authors found that drinking 500 mL of water or isotonic drink before the donation was useful in preventing (pre)syncopal reactions in donors, whereas isotonic drinks had the advantage of preventing delayed reactions and fatigue after the donation.…”
mentioning
confidence: 99%
“…There were approximately 400 total free text comments submitted, averaging seven comments per responder (range, 0-30). Each question averaged 13 free text comments (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. In general, the number of free text comments correlated with the complexity of the case (data not shown).…”
Section: Optional Responses and Commentsmentioning
confidence: 99%
“…Blood collection agencies use various mitigation strategies to reduce adverse events, including deferring donors at highest risk for adverse events, encouraging predonation fluid and salt loading, using applied muscle tension, optimizing the collection staff and environment, and ameliorating donationassociated fear and anxiety. [7][8][9][10][11][12][13][14] Beyond establishing baseline reaction rates (e.g., benchmarking), a robust donor HV system is necessary to assess the impact of diverse operational changes and mitigation strategies and to facilitate the reliable exchange of information and ideas.…”
mentioning
confidence: 99%
“…4 Bağış öncesi sıklıkla görülen baygınlık, baş dönmesi, sersemlikle kendini gösteren vasovagal reaksiyonlar sürecin olumsuz değerlendirilmesine neden olabilir. 18,19 Donasyon öncesi nabzın 90/dk ve üzerinde olması, diastolik kan basıncının 70 mm/Hg ve altında olması, 6 saat ve daha az uyuma, yemekten 4 saat ve daha uzun süre geçmiş olması, vasovagal reaksiyonlarda öngörülebilir özelliklerdendir. 18 Dolayısıyla uygun bilgilendirme, kan bağışından önce 500 ml su ya da izotonik sıvı tüketimi, kas germe egzersizi şeklinde yapılacak uygulamalarla olumsuz deneyimlerin azaltılması yanında, taşikardi, baş dönmesi, gerekçe belirtmeksizin bağıştan vazgeçme gibi nedenlerle olan retlerin önüne geçilebilir.…”
Section: Introductionunclassified
“…18 Dolayısıyla uygun bilgilendirme, kan bağışından önce 500 ml su ya da izotonik sıvı tüketimi, kas germe egzersizi şeklinde yapılacak uygulamalarla olumsuz deneyimlerin azaltılması yanında, taşikardi, baş dönmesi, gerekçe belirtmeksizin bağıştan vazgeçme gibi nedenlerle olan retlerin önüne geçilebilir. 19 Planlı bağış yapılacaksa kan bağışı ünitesinden bireylere randevu verilmesi ve donasyondan önce yapılması gerekenlere ilişkin "tam dinlenik halde bulunma", "2 saat öncesine kadar tam bir öğünle beslenmiş olma" gibi basit önerilerde bulunulması uykusuzluk/yorgunluk, açlık gibi nedenlerle olan retleri azaltabilir. 1,3 Yapılan çalışmalarda doğru yönetim ve düzenli takip sayesinde, ret yaşayan gönüllülerin bağış havuzuna tekrar kazandırılabileceği ve telefon görüşmesi, mail yada mesaj gibi farklı yaklaşımların donör geri kazanımında farklı dönüş hızı sağlayabileceği belirtilmektedir.…”
Section: Introductionunclassified